Contribution of type 2 diabetes to all-cause mortality, cardiovascular disease incidence and cancer incidence in white Europeans and South Asians: findings from the UK Biobank population-based cohort study - Karien Stronks; Anne Sillars; Stamatina Iliodromiti; Stuart Robert Gray; Mirthe Muilwijk; Heather Waddell; Rosemary Brown; Lyn Ferguson; Jason Martin Regnald Gill (BMJ Open Diabetes Research & Care)
Objective To investigate whether the health implications of having type 2 diabetes (T2D) were different in South Asian compared with white European participants.Research design and methods Prospective data from UK Biobank were used, and 457 935 participants of white European and 7102 of South Asian background were included. Cox proportional regression was performed to investigate the association between T2D and health outcome by ethnicity.Results Over a mean of 7.0 years (IQR 6.3–7.6) of follow-up, 12 974 participants had died, and 30 347 and 27 159 developed cardiovascular disease (CVD) and cancer, respectively. South Asians had a higher risk for CVD mortality (HR: 1.42, 95% CI 1.07 to 1.89) and incidence (HR: 1.78, 95% CI 1.63 to 1.94), but a decreased risk for cancer mortality (HR: 0.59, 95% CI 0.41 to 0.85) and incidence (HR: 0.80, 95% CI 0.70 to 0.92) compared with white Europeans. Compared with individuals without T2D, both white Europeans and South Asians with T2D had a higher risk for all-cause mortality (1.59 (1.48 to 1.71) vs 2.83 (1.76 to 4.53)), CVD mortality (2.04 (1.82 to 2.28) vs 4.40 (2.37 to 8.16)) and CVD incidence (1.37 (1.31 to 1.44) vs 1.60 (1.31 to 1.95)), respectively. However, the magnitude of the risk was higher for South Asians than white Europeans.Conclusions Although T2D was associated with a higher risk for all-cause mortality and CVD incidence and mortality, in both white Europeans and South Asians, the risk experienced by South Asians with T2D was higher than their white European counterparts.